Diseño de un sistema de costos para la “Heladeria la Chalupita”, ubicado en el cantón Latacunga provincia de Cotopaxi, parroquia Guaytacama, al primer trimestre del 2023. - Chancusig Casa, Luisa Fernanda (2024)
The current project named cost system for the “La Chalupita Ice Cream Shop, located in Latacunga province of Cotopaxi, Guaytacama parish, in the first quarter of 2023, was developed with the purpose of determining the production costs of pasted ice cream, four flavors and one just flavor. Bibliographic information was used and costing was determined through production orders since it is the system that most focuses on the characteristics of the company, which will help obtain real and truthful information for correct decision making. It is necessary to mention that the company did not use forms of costing, which caused a total ignorance of production costs, the determination of the sales price and therefore the profit generated. The methodology used was handled from a quantitative approach, applying different techniques such as documentary, field and analytical research through surveys, interviews and observation sheets. Data and information related to production costs were collected. The production order cost system implemented at the Heladería la Chalupita reveals disagreements between empirical costs and real production costs. For example, the empirical unit cost of frozen ice cream is $0.50, while the actual cost is $0.56. Similarly, the empirical unit cost of flavored ice cream is $0.24, but the actual cost is slightly higher at $0.25. Furthermore, the empirical unit cost of single flavor ice cream is estimated at $0.25, while the real value of the unit cost does not vary, remaining at $0.25. To conclude, when applying the cost system, it revealed discrepancies that originate from the empirical calculation of costs, attributable to losses of raw materials and errors in the estimation of cost elements. This has resulted in a 4% variation in the total production cost.